Kynurenic Acid Protects against Thioacetamide-Induced Liver Injury in Rats - Sebastian Marciniak; Artur Wnorowski; Katarzyna Smolińska; Beata Walczyna; Waldemar Turski; Tomasz Kocki; Piotr Paluszkiewicz; Jolanta Parada-Turska (Analytical Cellular Pathology)
Acute liver failure (ALF) is a life-threatening disorder of liver function. Kynurenic acid (KYNA), a tryptophan metabolite formed along the kynurenine metabolic pathway, possesses anti-inflammatory and antioxidant properties. Its presence in food and its potential role in the digestive system was recently reported. The aim of this study was to define the effect of KYNA on liver failure. The Wistar rat model of thioacetamide-induced liver injury was used. Morphological and biochemical analyses as well as the measurement of KYNA content in liver and hepatoprotective herbal remedies were conducted. The significant attenuation of morphological disturbances and aspartate and alanine transaminase activities, decrease of myeloperoxidase and tumor necrosis factor-α, and elevation of interleukin-10 levels indicating the protective effect of KYNA in thioacetamide (TAA) - induced liver injury were discovered. In conclusion, the hepatoprotective role of KYNA in an animal model of liver failure was documented and the use of KYNA in the treatment of ALF was suggested.